Association Between Nutritional Status and Anemia Among Under-Five Children at Abdul Manap Regional Hospital, Jambi - Syifa Putri Mutiara Kansya; Fitri Asymida; Armaidi Darmawan; Esa Indah Ayudia (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Anemia and undernutrition frequently coexist in early childhood and may reinforce one another through inadequate nutrient intake, impaired erythropoiesis, infection, and reduced appetite. This study analyzed the association between nutritional status and anemia among children under five years of age at Abdul Manap Regional Hospital, Jambi. An analytical observational study with a retrospective case-control approach used secondary medical-record data from 2019–2023. Ninety-two children were included, comprising 46 anemia cases and 46 non-anemia controls. Nutritional status was assessed using weight-for-height indicators based on World Health Organization child growth standards. Univariate analysis described participant characteristics, and the Chi-square test with an odds ratio estimated the association between nutritional status and anemia. Most participants were aged 13–36 months (55.4%) and male (63.0%). Undernutrition predominated in the anemia group (56.5%), whereas normal nutritional status predominated among controls (63.0%). Nutritional status was significantly associated with anemia (p=0.002); undernourished children had 4.31 times the odds of anemia compared with children with normal or excess nutritional status (95% CI: 1.79–10.39). These findings support integrated nutritional assessment, caregiver education, and routine anemia screening for young children.